(untitled) (Research, Society and Development, 2020)
Objective: To build and validate an instrument to assess quality of life and diagnostic aid for telogen effluvium. Methodology: Seven experts in the field of dermatology and / or trichology were selected who met the criteria adapted from Fehring (1994). The Likert scale (1932) was used to assess the protocol items for clarity, conciseness, understandable language and applicability. For the validation of the instrument, it was analyzed how the concepts are adequately represented and the possibility or not of being able to capture the domain of the desired content. The item’s relevance criterion was at least 80% agreement between the judges. Result: The average professional experience of the judges was 10.42 years. The names of the judges or any characteristic that identifies them were spared the results of the study. In general, the items evaluated scored 3 and 4 in more than 80% of the cases, which was considered adequate according to the item’s pertinence analysis. Small changes were made for better literacy according to the judges’ suggestions. Conclusion: In the study, the clarity, the conciseness of the text, the understanding of the language and the applicability of the instrument were verified, obtaining satisfactory levels of agreement. Most of the judges suggestions were accepted. Therefore, the protocol can be used to identify individuals who have capillary diseases aggravated by stress, such as telogen effluvium, as well as the biopsychosocial impact of dermatosis on the quality of life of its patients.